Bone marrow‐derived mesenchymal stem cells enhance autophagy via PI3K/AKT signalling to reduce the severity of ischaemia/reperfusion‐induced lung injury. Issue 10 (14th July 2015) - Li, Jing; Zhou, Jian; Zhang, Dan; Song, Yuanlin; She, Jun; Bai, Chunxue
Abstract Autophagy, a type II programmed cell death, is essential for cell survival under stress, e.g. lung injury, and bone marrow‐derived mesenchymal stem cells (BM‐MSCs) have great potential for cell therapy. However, the mechanisms underlying the BM‐MSC activation of autophagy to provide a therapeutic effect in ischaemia/reperfusion‐induced lung injury (IRI) remain unclear. Thus, we investigate the activation of autophagy in IRI following transplantation with BM‐MSCs. Seventy mice were pre‐treated with BM‐MSCs before they underwent lung IRI surgery in vivo. Human pulmonary micro‐vascular endothelial cells (HPMVECs) were pre‐conditioned with BM‐MSCs by oxygen‐glucose deprivation/reoxygenation (OGD) in vitro. Expression markers for autophagy and the phosphoinositide 3‐kinase/protein kinase B (PI3K/Akt) signalling pathway were analysed. In IRI‐treated mice, administration of BM‐MSCs significantly attenuated lung injury and inflammation, and increased the level of autophagy. In OGD‐treated HPMVECs, co‐culture with BM‐MSCs attenuated endothelial permeability by decreasing the level of cell death and enhanced autophagic activation. Moreover, administration of BM‐MSCs decreased the level of PI3K class I and p‐Akt while the expression of PI3K class III was increased. Finally, BM‐MSCs‐induced autophagic activity was prevented using the inhibitor LY294002. Administration of BM‐MSCs attenuated lung injury by improving the autophagy level via the PI3K/Akt signalling pathway. These findings provide further understanding of the mechanisms related to BM‐MSCs and will help to develop new cell‐based therapeutic strategies in lung injury.